2015
DOI: 10.1088/0953-2048/28/12/124005
|View full text |Cite
|
Sign up to set email alerts
|

Test of 60 kA coated conductor cable prototypes for fusion magnets

Abstract: Coated conductors could be promising materials for the fabrication of the large magnet systems of future fusion devices. Two prototype conductors (flat cables in steel conduits), each about 2 m long, were manufactured using coated conductor tapes (4 mm wide) from Super Power and SuperOx, with a total tape length of 1.6 km. Each flat cable is assembled from 20 strands, each strand consisting of a stack of 16 tapes surrounded by two half circular copper profiles, twisted and soldered. The tapes were measured at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 21 publications
5
68
0
Order By: Relevance
“…The difference between the T cs values defined at these criteria depends on the m-value of the T − E transition. In accordance with the test results of the HTS cable prototype [3], this difference can be estimated as ≈2 K at 12 T and for operating currents between 50 kA to 60 kA.…”
Section: A T Cs Calculationsupporting
confidence: 84%
See 3 more Smart Citations
“…The difference between the T cs values defined at these criteria depends on the m-value of the T − E transition. In accordance with the test results of the HTS cable prototype [3], this difference can be estimated as ≈2 K at 12 T and for operating currents between 50 kA to 60 kA.…”
Section: A T Cs Calculationsupporting
confidence: 84%
“…The critical current of the cable I c is affected by the self-field effect even at high background magnetic fields, but this effect is almost completely compensated by the angular dependence of the tape's critical current I t c at least in the operating conditions from 40 kA to 70 kA and from 8 T to 12 T [3]. Eventually, a simple and reliable approach to estimate I c is to sum up I t c corresponding to the perpendicular field component.…”
Section: A T Cs Calculationmentioning
confidence: 99%
See 2 more Smart Citations
“…With the development in the properties of high temperature superconducting (HTS) conductors, the HTS magnet could be considered as potential Tokamak magnet components with the advantages of higher operation temperature and critical current density [1][2][3]. At present, the application of HTS in fusion devices mainly focuses on the design and fabrication of high temperature superconducting high current conductor [4][5][6][7][8], the design and fabrication of high temperature superconducting current lead [9,10], and the concept design and small model fabrication of HTS magnet [11,12]. It was revealed that when the TF coil system operates at the temperature range of 10 to 20 K, accordingly, the manufacturing and operating cost of the device could be reduced [13].…”
Section: Introductionmentioning
confidence: 99%